Development of Contextual Learning Methods in Islamic Religious Education Learning - Firmansyah; Siti Fatimah; Mukti Ali; Zulkipli; Rabial Kanada (International Journal of Global Sustainable Research, 2023)
This study is intended to examine the urgency of developing PAI learning methods from conventional to contextual. The study in the research, among others, discusses the basis of the development of learning methods, the characteristics of conventional learning methods, and the characteristics of contextual learning methods. The method used in the research is a literature study of primary sources and secondary sources, in the form of previous research results which are research reports and articles published in scientific journals. The results showed that to increase the effectiveness of PAI learning, it is necessary to shift from conventional methods to contextual methods. With contextual methods, teachers can relate PAI materials to real situations, illustrate their relevance in everyday life, and encourage students to bridge theoretical knowledge with its application in their lives. The use of contextual methods in PAI learning in schools is an innovative effort to enhance the role of Islamic education in educational institutions, with the main objective of forming Islamic character in students. The study recommends that PAI teachers can apply contextual methods in PAI learning so that the results of PAI learning can be more meaningful for students' lives.